Nuevos temas éticos en la ciencia económica (Cultura Económica, 2019)
Jose Enrique Miguens considers, in the first place, the relationship between morals and economics, starting from the dissociation introduced between them by the Enlightenment. Then he goes through the historical changes in economics and ethics. In the second place, heanalyses the re-entry of morals into economics, proposing a dialogue with the rest of the human disciplines. Finally, he attempts to enumerate the elements that allow the introduction of moral considerations in economic analysis, taking new concepts into account. The article shows the need to lead economics to its true aims, putting the human person in the first place.
Keywords: Ethics; Amartya Sen; dialogue; development